Features of the Karst-Solifluction Processes in Rocks of the Sokhsolokhskiy Graben Trough - P. V. Nekrasov (Vestnik Permskogo Universiteta: Seriâ Geologiâ)
The article considers the features of the formation of karst-solifluction reservoirs in the eastern part of the Sokhsolokhskiy graben-shaped Trough, and traces the stages of their development. The spatial and genetic relationship of micro-components, elements of "traps" of synformal structures, depressions with manifestations of the hydrofactor and features of the geodynamic development of the platform in the Devonian-Triassic Epoch has been established. The main relationship of spatial placement of karst reservoirs with deflections and depressions, and hydrothermal ore mineralization was revealed.